Caregiving burden and depression among caregivers of people living with HIV/AIDS attending anti-retroviral therapy unit of Kaski - Gurung, Bishnu; Poudel, Anju; Sharma, Rasna; Baral, Samjhana (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: A descriptive cross-sectional study was conducted among caregivers of people living with HIV/AIDS (PLHIV/AIDS) attending anti-retroviral therapy (ART) unit of Kaski. The study aimed to assess the caregiving burden and depression and their relationship among caregivers of PLHIV/AIDS. Methods: Purposive sampling technique was adopted and total 238 caregivers were interviewed. Standard tool Zarit Burden Inventory and Beck Depression Inventory was used to assess burden and depression among caregivers of HIV/AIDS. For data analysis, data were entered in EPI 3.1 version and then exported to SPSS version 16.0. Descriptive statistics frequency, percentage, mean and standard deviation were calculated and for inferential analysis, Man-Whitney U test and Kruskal Wallis H test was used. Results: The study revealed about one third of the caregivers experienced caregiving burden and few have depression. There is statistically significant difference in burden of caregivers with regard to gender, occupation, family income, relation with patient and HIV status. Similarly, caregiver burden was found to be high if the PLHIV/AIDS was male and age ≤38 years old. The study showed significant difference in caregiver’s depression with caregiver’s burden and moderate positive correlation between caregiver’s burden and depression. Conclusions: The study concluded burden and depression among caregivers of PLHIV/AIDS is alarming. Burden was found to be high in caregivers who are female, unemployed, having sufficient family income, family members and those who have HIV positive status. Regular Screening program among caregivers for depression should be conducted in anti-retroviral therapy unit on periodic time interval.